Control of glycaemia and its related factors in patients with type 2 diabetes, north of Iran: generalized linear mixed models and prevalence of overdispersion in patients - Samaneh Hosseinzadeh; Saeideh Davar (Health Science Monitor)
Background & Aims:  Glycemic control is very important to prevent or suspend complications in patients with type 2 diabetes (PT2D). The aim of this study was to investigate the status of glycemic control and its related factors in patients with type 2 diabetes (PT2D) based on HbA1c, fasting blood glucose, and non-fasting blood glucose levels in Golestan Province, Northern Iran. Materials & Methods: The study employed a retrospective cohort design, collecting data longitudinally and retrospectively from 500 patients with type 2 diabetes (PT2D) who were referred to health centers in Golestan Province between 2013 and 2016 (every three months). The study focused on hbA1c, fasting blood glucose (FBG), and non-fasting blood glucose (NFBG) levels, which were recorded as binary data (1 = abnormal; if the value exceeded its cut point), indicating a lack of control over these markers. The Index of Glycemic Control (IGC) was calculated for each patient, with an IGC of 3 indicating inadequate glycemic control. Related factors were analyzed using a generalized linear mixed model with a beta-binomial distribution. Results: The results indicated that 93% of patients had an Index of Glycemic Control (IGC) equal to 3 in the first year, and this percentage decreased to 60.7% by the third year. The downward trend in IGC was gradual over the three years. Factors contributing to poor glycemic control included younger age, shorter duration of diabetes care, elevated blood lipid levels, high blood pressure, insulin therapy, and overweight or obesity as indicated by BMI. Conclusion: The results obtained from the samples in Golestan Province indicate inadequate blood glucose control and poor quality of care. It is essential to implement more intensive diabetes management strategies within national healthcare plans.